ANALYSIS OF THE INFLUENCE OF GREEN INTELLECTUAL CAPITAL, LEVERAGE RATIO AND PROFIT QUALITY ON COMPANY VALUE WITH COMPANY SIZE AS A MODERATOR - Eko Supriyanto; Joko Setiawan; Tris Sudarto (ZILLZELL MEDIA PRIMA, 2025)
This study aims to analyze the effects of Green Intellectual Capital (GIC), leverage ratio (Debt to Asset Ratio - DAR), and earnings quality on the firm value of palm oil plantation companies listed on the Indonesia Stock Exchange (IDX). Furthermore, it investigates the moderating role of firm size in these relationships. The research employs a quantitative approach using panel data from publicly listed palm oil companies on the IDX from 2017 to 2024. Data were analyzed using panel data regression analysis with the EViews application to test the direct effects and moderating effects. The results indicate that: (1) GIC has a positive and significant effect on firm value; (2) Leverage ratio (DAR) has a negative and significant effect on firm value; (3) Earnings quality has no significant effect on firm value; (4) Firm size does not directly affect firm value but acts as a significant moderator; (5) Firm size weakens the positive effect of GIC on firm value; (6) Firm size strengthens the negative effect of leverage ratio on firm value, turning it less negative or positive in context; and (7) Firm size does not moderate the relationship between earnings quality and firm value. This study provides novel insights into the dual and contrasting moderating role of firm size in an emerging market context, specifically showing how it dampens the value of sustainability disclosures (GIC) while amplifying the acceptability of financial leverage. Managers should strategically disclose GIC to enhance valuation and adopt prudent leverage policies. For larger firms, it is crucial to communicate their sustainability efforts more effectively to maintain their premium, as investors' higher expectations can diminish the marginal value of these disclosures.